The Effects of Video-Assisted Jigsaw Cooperative Learning on Students’ Biology Learning Achievement and Critical Thinking Skills - Yendrita, Yendrita; Nengsi, Sri; Usmadi, Usmadi; Mulyanda, Sandy (ISEJ : Indonesian Science Education Journal, 2026)
Many studies have reported the effectiveness of jigsaw cooperative learning in science education; however, scholars have paid little attention to integrating this model with digital learning media to enhance students’ learning outcomes and critical thinking skills. Therefore, to fill this gap, this study aims to examine the influence of video-assisted jigsaw cooperative learning on students’ learning achievement and critical thinking skills in biology instruction. This quasi-experimental study, using a pretest-posttest control group design, involved tenth-grade students in Phase E, at one of the schools in Lima Puluh Kota Regency, West Sumatra, Indonesia. The number of students in each experimental and control group was 30. The data were obtained from learning achievement and critical thinking tests administered before and after the treatments. The parametric statistics (ANCOVA and MANCOVA tests), were used to analyze the data. The results showed that students in the video-assisted jigsaw cooperative learning group demonstrated significantly higher biology learning achievement scores after controlling for pretest scores, F(1, 57) = 4919.00, p < .001, η² = .989. Similarly, students in the experimental group showed significantly higher critical thinking skill scores after controlling for pretest scores, F(1, 57) = 7596.00, p < .001, η² = .993. Furthermore, the results of the MANCOVA test indicated a significant simultaneous effect on both dependent variables, Wilks’ Λ = .007, F(2, 55) = 4190.00, p < .001, partial η² = .993. These findings suggest that video-assisted jigsaw cooperative learning has the potential to support students’ academic achievement and critical thinking skills in biology.